2022
DOI: 10.1021/acs.jpcc.2c01656
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Detection of Isolated Nanoscale Defects in 2D Transition Metal Dichalcogenides

Abstract: We show that nanometer and sub-nanometer scale defects in two-dimensional transition metal dichalcogenides can be detected electrochemically using scanning electrochemical cell microscopy (SECCM). We detect isolated anomalous electrochemical responses for the hexaammineruthenium ([Ru­(NH3)6]3+/2+) redox couple on mono-, bi-, and trilayer regions of mechanically exfoliated MoS2. These anomalous sample points display faster electrochemical kinetics, with a diffusion-limited current plateau, compared to the surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Transition metal dichalcogenides (TMDs), such as MoSe 2 and WSe 2 , are promising candidates in novel high-performance nanoelectronic and optoelectronic devices due to their alluring properties. In general, intrinsic defects and unintentional impurities during the growth of the materials are unavoidable, and they dramatically affect the physical and chemical properties of the materials. On the other hand, the functionality of semiconductors depends essentially on whether enough free carriers can be introduced by doping. , Therefore, the prerequisite for designing and optimizing high-performance devices is to have deep understanding of the properties of defects in materials.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal dichalcogenides (TMDs), such as MoSe 2 and WSe 2 , are promising candidates in novel high-performance nanoelectronic and optoelectronic devices due to their alluring properties. In general, intrinsic defects and unintentional impurities during the growth of the materials are unavoidable, and they dramatically affect the physical and chemical properties of the materials. On the other hand, the functionality of semiconductors depends essentially on whether enough free carriers can be introduced by doping. , Therefore, the prerequisite for designing and optimizing high-performance devices is to have deep understanding of the properties of defects in materials.…”
Section: Introductionmentioning
confidence: 99%
“…This was already highlighted for graphene on Nafion and films on electrodes in Technical and Theoretical Developments above. When electrochemical activity varies locally across a 2D material, this may be indicative of a key role of defect sites on the basal surface, , and SECCM can be used to estimate the defect size. SECCM revealed that the basal planes of MoS 2 (1H phase and 2H phase) shows catalytic activity.…”
Section: High-throughput Scanning Electrochemical Cell Microscopymentioning
confidence: 99%
“…SECCM was extensively used to acquire high spatial resolution maps to elucidate differences in electrochemical activity between phases and grain boundaries of many polycrystalline materials such as platinum, , palladium, gold, copper, or boron-doped diamond surfaces. SECCM in tandem with simulations was used to spatially map electron-transfer kinetics parameters, like the Tafel slope and the heterogeneous electron-transfer rate constant. The sensitivity of the SECCM for local activity measurement was demonstrated and used to differentiate the surface activities of glassy carbon and graphite. Two-dimensional materials, such as graphene, MoS 2 , , and other transition metal dichalcogenides , were also investigated by SECCM. The studies demonstrated the presence of heterogeneous activity at different sites such as defects, edges, and basal planes.…”
Section: Backstage: Principles and Applicability Of Operando Sepmmentioning
confidence: 99%